Shakespeare for children, with ebook eaudiobook - Lamb, Charles (Tantor Media, 2008)
Originally written to be an "introduction to the study of Shakespeare," Shakespeare for Children is much more entertaining than that—some of Shakespeare's best-loved plays, comic and tragic, are retold in a clear and robust style. Charles and Mary Lamb introduce children to the magic of Shakespeare with these ten favorite tales. Although simplified, these stories don't underestimate young readers; they keep the complexity, twists of plot, and turns of fate found in the originals. And their literary quality has made them popular and sought-after ever since their first publication in 1807. Included in this edition are: —"The Tempest" —"A Midsummer Night's Dream" —"Much Ado About Nothing" —"King Lear" —"Macbeth" —"The Taming of the Shrew" —"Twelfth Night; or, What You Will" —"Romeo and Juliet" —"Hamlet, Prince of Denmark" —"Othello"